Post-conditionality politics and administrative reform: reflections on the cases of Uganda and Tanzania - Harrison, Graham (2001)
This article contributes to the discussion of the nature of external intervention in the reform processes of indebted states. Looking at administrative reform in Uganda and Tanzania, it is argued that external involvement in sub-Saharan Africa is becoming increasingly differentiated. For some states - including the two cases dealt with here - a key set of continuities and changes allows us to conceptualize a regime of post-conditionality. Post-conditionality regimes exist where extreme external dependence and economic growth produce a set of political dynamics in which external-national distinctions become less useful, in which there emerges a set of unequal mutual dependencies, and in which donor/creditor involvement in reform becomes qualitatively more intimate, pervading the form and processes of the state. Details of this dispensation are provided in an analysis of key ministries and key interventions by donors/creditors. The article finishes by considering the contradictions of the post-conditionality regime, and its prospects. - Reproduced
Keywords: Administrative reform - Tanzania; Administrative reform - Uganda; Administrative reform